Panduan Teknik Assertive Training Bermuatan Nilai Budi Pekerti Serat Wulangreh untuk Meningkatkan Kecerdasan Emosional Siswa - Srianturi, Yanuari; Setyoningsih, Yunita Dwi; Afriliyanto, Agus; Fuadina, Nabila (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This research aims to produce a product in the form of a manual for assertive training techniques containing moral values in wulangreh fiber to increase emotional intelligence in junior high school students that is suitable according to the assessment of experts and potential users. This research uses the research and development design from Borg & Gall which modified the ten stages into three stages pre-development, development and post-development, but due to time. The technique used to analyze expert test data and test prospective users uses Aiken's content validity. Data collection instruments include expert test assessments, prospective user assessments, interviews and observations. Analysis of the test results shows that regarding the specific content of the guidebook, guidance and counseling material experts obtained a validation index of 0.83 (high), cultural experts obtained a validation index of 0.84 (high), prospective users obtained a validation index of 0.82 (high), while testing on the specific guidebook format by media experts obtained index of 0.86 (high).